The survey of nurse's knowledge and attitude toward cancer pain management: Application of Health Belief Model - Shahnazi, Hossein (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Effective cancer pain management requires accurate knowledge, attitudes, and assessment skills. The purpose of this study was to obtain information about the knowledge and attitudes of nurses concerning cancer pain management with the use Health Belief Model (HBM) as conceptual framework. MATERIALS AND METHODS: The study was a descriptive survey and included 98 randomly selected nurses from Alzahra hospital, Isfahan, Iran. A self-administered questionnaire which was designed on the basis of HBM was used to collect the data. Knowledge, attitudes, and HBM constructs regarding cancer pain were the main research variables. The obtained data were analyzed by SPSS (version11.5) using descriptive statistics, independent t–test, and Pearson correlation at the significant level of α=0.05. RESULTS: Ninety-eight nurses aged 38.7 ± 7.04 years were studied in this survey. From the 10 pain knowledge questions assessed, the mean number of correctly answered question was 61.2 (SD=16.5), with a range of 30–100. There was a direct correlation between knowledge and attitude of nurses with HBM constructs except for perceived barriers and perceived threat. Among the HBM constructs, the highest score was related to self-efficacy with mean score of 87.2 (SD=16.4). CONCLUSIONS: The findings support the concern of inadequate knowledge and attitudes in relation to cancer pain management. We believe that basic and continuing education programs may improve the knowledge level of nursing about pain management.